Optimizing baseball defensive alignments through integer programming and simulation. (3rd April 2017) - Easton, Todd; Becker, Kyle
Abstract: Baseball is an incredibly complex game in which the manager makes numerous difficult decisions. This paper describes a stochastic integer program that determines the best defensive starting positions to minimize the expected batting average of a particular player. To test this optimal defense against other standard Major League Baseball ® defenses, a simulation is created. A computational study demonstrates how the optimal defense can be used to decrease Derek Jeter's batting average in a statistically significant manner.